Federal Regulations Affecting Use of Pesticides - Frederick M. Fishel (EDIS)
PI-131, a 7-page fact sheet by Frederick M. Fishel, describes ten federal acts, requirements and standards regulating the use of pesticides. Includes a list of acronyms and references. Published by the UF Department of Agronomy, July 2006.